A novel optical thermometry based on the energy transfer from charge transfer band to Eu3+-Dy3+ ions - Jing Wang (Nature Portfolio, 2017)
Abstract Optical thermometry based on the up-conversion intensity ratio of thermally coupled levels of rare earth ions has been widely studied to achieve an inaccessible temperature measurement in submicron scale. In this work, a novel optical temperature sensing strategy based on the energy transfer from charge transfer bands of W-O and Eu-O to Eu3+-Dy3+ ions is proposed. A series of Eu3+/Dy3+ co-doped SrWO4 is synthesized by the conventional high-temperature solid-state method. It is found that the emission spectra, emission intensity ratio of Dy3+ (572 nm) and Eu3+ (615 nm), fluorescence color, lifetime decay curves of Dy3+ (572 nm) and Eu3+ (615 nm), and relative and absolute sensitivities of Eu3+/Dy3+ co-doped SrWO4 are temperature dependent under the 266 nm excitation in the temperature range from 11 K to 529 K. The emission intensity ratio of Dy3+ (572 nm) and Eu3+ (615 nm) ions exhibits exponentially relation to the temperature due to the different energy transfer from the charge transfer bands of W-O and Eu-O to Dy3+ and Eu3+ ions. In this host, the maximum relative sensitivity Sr can be reached at 1.71% K−1, being higher than those previously reported material. It opens a new route to obtain optical thermometry with high sensitivity through using down-conversion fluorescence under ultraviolet excitation.